Propofol Inhibits Ischemia/Reperfusion-Induced Cardiotoxicity Through the Protein Kinase C/Nuclear Factor Erythroid 2-Related Factor Pathway - Li, Shengqiang; Lei, Zhen; Zhao, Meng; Hou, Yonghao; Wang, Di; Xu, Xingli; Lin, Xiaowen; Li, Jingxin; Tang, Shuhai; Yu, Jingui; Meng, Tao (Frontiers in Pharmacology, 2021)
Both hydrogen peroxide (H2O2, H) and ischemia/reperfusion (I/R) can damage cardiomyocytes, which was inhibited by propofol (P). The present research was designed to examine whether propofol can reduce myocardial I/R injury by activating protein kinase C (PKC)/nuclear factor erythroid-2-related factor 2 (NRF2) pathway in H9C2 cells and rat Langendorff models. H9C2 cells were disposed of no reagents (C), H2O2 for 24 h (H), propofol for 1 h before H2O2 (H+P), and chelerythrine (CHE, PKC inhibitor) for 1 h before propofol and H2O2 (H+P+CHE). N = 3. The PKC gene of H9C2 was knocked down by siRNA and overexpressed by phorbol 12-myristate 13-acetate (PMA, PKC agonist). The cell viability and the expressions of PKC, NRF2, or heme oxygenase-1(HO-1) were evaluated. Propofol significantly reduced H9C2 cell mortality induced by H2O2, and significantly increased NRF2 nuclear location and HO-1 expression, which were restrained by siRNA knockout of PKC and promoted by PMA. Rat hearts were treated with KrebsHenseleit solution for 120 min (C), with (I/R+P) or without (I/R) propofol for 20 min before stopping perfusion for 30 min and reperfusion for 60 min, and CHE for 10 min before treated with propofol. N = 6. The levels of lactate dehydrogenase (LDH), superoxide dismutase (SOD), and creatine kinase-MB (CK-MB) in perfusion fluid and antioxidant enzymes in the myocardium were assessed. I/R, which increased LDH and CK-MB expression and reduced SOD expression, boosted the pathological damage and infarcts of the myocardium after reperfusion. However, propofol restrained all these effects, an activity that was antagonized by CHE. The results suggest that propofol pretreatment protects against I/R injury by activating of PKC/NRF2 pathway.